Herpesvirus infection and infectious mononucleosis - E. V. Sharipova; I. V. Babachenko (Журнал инфектологии)
In this review we present current information on various aspects of infectious mononucleosis in children. Based on the analysis of scientific literature highlights the major etiological factors that lead to the development of this disease. The paper describes the clinical and laboratory features of infectious mononucleosis caused by Epstein-Barr virus, cytomegalovirus, human herpes virus type VI. Presents literature data on the impact of herpes infection on the development of mononucleosis. Showing modern aspects of an integrated diagnosis of herpesvirus infection in infectious mononucleosis in children.